The $74 million Nobo Jatra (New Beginning) USAID-funded project includes PIM findings to improve child nutrition in poor coastal areas of Bangladesh - CGIAR Research Program on Policies, Institutions, and Markets (2018)
The results of the Transfer Modality Research Initiative informed the design of the conditional cash transfer of the Nobo Jatra (New Beginning) project, a 2016-2020 $74 million project funded by USAID and implemented by World Vision International in Southern Bangladesh.